ANALYZING THE THEORIES OF CONTRIBUTING FACTORS TO PUBLIC ACCIDENTS IN THE MALAYSIAN CONSTRUCTION INDUSTRY: A BRIEF OVERVIEW OF CONSTRUCTION WORKERS - Azil, Nurul Ain Shuhada; Jabar, Izatul Laili; Che Ahmad, Asmalia (Journal of Surveying, Construction and Property, 2023)
In Malaysia, the construction industry faces a wide range of challenges, one of which is the public accident and injuries at the construction sites. Construction is well known as a labor-intensive industry, thus the need to provide awareness to construction workers regarding public accidents should be the main consideration during the project implementation. On the other hand, the unsafe acts of construction workers were also considered major contributors to public accidents and injuries at construction sites. Therefore, this study aims to analyze the factors that are related to the construction workers which contribute to public accidents in the Malaysian Construction Industry. The researcher has devised two (2) objectives to accomplish the study's purpose; (1) to explore public accident cases in the construction industry, and (2) to identify the factors related to construction workers that contribute to public accidents in the Malaysian construction industry. A snowballing technique was applied through the reference list of reviewing previous papers and the findings reveal thirty-one (31) factors that are related to the construction workers which lead to public accidents and injury. The contribution of this study can therefore be a mechanism for construction workers to manage safe conditions at the workplace and raise awareness in comprehending factors that emerge in the construction industry.